Mapping cardiopulmonary dynamics within the microvasculature of the lungs using dissolved (129)Xe MRI - Niedbalski, Peter J. (J Appl Physiol (1985), 2020)
Magnetic resonance (MR) imaging and spectroscopy using dissolved hyperpolarized (HP) (129)Xe have expanded the ability to probe lung function regionally and noninvasively. In particular, HP (129)Xe imaging has been used to quantify impaired gas uptake by the pulmonary tissues. Whole-lung spectroscopy has also been used to assess global cardiogenic oscillations in the MR signal intensity originating from (129)Xe dissolved in the red blood cells of pulmonary capillaries. Herein, we show that the magnitude of these cardiogenic dynamics can be mapped three dimensionally using radial MRI, because dissolved (129)Xe dynamics are encoded directly in the raw imaging data. Specifically, 1-point Dixon imaging is combined with postacquisition keyhole image reconstruction to assess regional blood volume fluctuations within the pulmonary microvasculature throughout the cardiac cycle. This “oscillation mapping” was applied in healthy subjects (mean amplitude 9% of total RBC signal) and patients with pulmonary arterial hypertension (PAH; mean 4%) and idiopathic pulmonary fibrosis (IPF; mean 14%). Whole-lung mean values from these oscillation maps correlated strongly with spectroscopy and clinical pulmonary function testing, but exhibited significant regional heterogeneity, including gravitationally dependent gradients in healthy subjects. Moreover, regional oscillations were found to be sensitive to disease state. Greater percentages of the lungs exhibit low-amplitude oscillations in PAH patients, and longitudinal imaging shows high-amplitude oscillations increase significantly over time (4–14 mo, P = 0.02) in IPF patients. This technique enables regional dynamics within the pulmonary capillary bed to be measured, and in doing so, provides insight into the origin and progression of pathophysiology within the lung microvasculature. NEW & NOTEWORTHY Spatially heterogeneous abnormalities within the lung microvasculature contribute to pathology in various cardiopulmonary diseases but are difficult to assess noninvasively. Hyperpolarized (129)Xe MRI is a noninvasive method to probe lung function, including regional gas exchange between pulmonary air spaces and capillaries. We show that cardiogenic oscillations in the raw dissolved (129)Xe MRI signal from pulmonary capillary red blood cells can be imaged using a postacquisition reconstruction technique, providing a new means of assessing regional lung microvasculature function and disease state.